FACIAL SKIN LINES (Iraqi Journal of Medical Sciences, 2016)
Throughout ages, skin lines had been examined by anatomists and surgeons with a great controversy about the consistency of each. None of them is considered to be the gold standard for surgical incisions. Furthermore, skin lines are not often fully understood and being misquoted over and over in literatures. Various methods had been adopted; from a simple pinch to 3D scan computerized models. Different explanations had been given for the causes of formation and variation of those lines.Keywords: Skin lines, Langer's lines, tension lines.
Keywords: Skin lines; Langers lines; tension lines